2001
DOI: 10.1097/00007632-200109150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bracing in Male Patients With Idiopathic Scoliosis

Abstract: Bracing of male patients with idiopathic scoliosis is ineffective. Curves measuring > or =30 degrees are very likely to progress to surgery, especially in immature patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
100
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 12 publications
3
100
1
1
Order By: Relevance
“…Brace compliance was potentially responsible for the disparity of success between males and females treated with bracing [22,59] and may explain the similar results of noncompliant patients with the natural history. Numerous studies have demonstrated compliant brace wear leads to successful results, yet much of the data, as acknowledged by the authors, is subjective based on incomplete assessments of compliance such as office notes, questionnaires, or phone or office interviews [22,30,34,58]. Thus, this has led some to doubt the efficacy of bracing and the need for objective compliance measures [51].…”
Section: Bracing Difficultiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Brace compliance was potentially responsible for the disparity of success between males and females treated with bracing [22,59] and may explain the similar results of noncompliant patients with the natural history. Numerous studies have demonstrated compliant brace wear leads to successful results, yet much of the data, as acknowledged by the authors, is subjective based on incomplete assessments of compliance such as office notes, questionnaires, or phone or office interviews [22,30,34,58]. Thus, this has led some to doubt the efficacy of bracing and the need for objective compliance measures [51].…”
Section: Bracing Difficultiesmentioning
confidence: 98%
“…Poor compliance with wear schedules is a major recurring theme in the braced patient, particularly males. Karol [22] found only 38% of males were compliant with brace wear, and 74% progressed 6°with nearly half reaching a surgical threshold of 50°. Immature Risser status related to both progression and surgery with greater than 80% progressing a minimum 6°and half reaching surgery.…”
Section: Bracing Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher rates of atypical curves and failure of bracing treatment have been reported in male patients [25,62]. A genomic screening study of chromosome 17 in a subgroup of families in which affected males had undergone surgery showed that a specific genetic locus (d17s975 and d17s2196) was significantly associated with the familial IS phenotype [13].…”
Section: Geneticsmentioning
confidence: 99%
“…Several uncontrolled retrospective case series of braced patients have been published; those reporting surgical rates demonstrate widely varying outcomes ranging from 7% to 43%. [10][11][12][13][14][15][16][17][18][19][20][21][22] Two studies have simultaneously compared untreated and braced curves. 2,3 Fernandez-Feliberti et al 2 reported a 26% surgery rate in the braced cases compared with 38% in the observed cases.…”
mentioning
confidence: 99%